Pengaruh motivasi, lingkungan kerja, dan stres kerja terhadap kinerja karyawan - Mugni Jayadi, Ramadhan; Liana, Lie (Fair Value: Jurnal Ilmiah Akuntansi dan Keuangan, 2022)
This study aims to analyze the effect of motivation, work environment and work stress on employee performance. The population in this study were employees of PT. Cipta Niaga Semesta, totaling 110 people. This type of research is quantitative. The data collection method in this study used a survey with an instrument in the form of a questionnaire distributed to respondents. The method used in this assessment is multiple regression analysis used to explain the influence between variables. Data were analyzed using factor analysis to test the validity of each question item, and reliability test using Cronbach alpha. The results of hypothesis testing indicate that motivation has a positive and significant effect on employee performance, the work environment has a positive and significant effect on employee performance and work stress has a negative and significant effect on employee performance.